PENATAAN RUANG KELOLA KOTA SURABAYA TERKAIT RUANG UNTUK MASYARAKAT MISKIN - Marcel Handoko (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
This study examines the relevance of Surabaya City's 2024 spatial planning policy to the National Strategic Project (PSN) development plan, which adheres to the principles of integration, sustainability, and spatial equity, in accordance with Law Number 26 of 2007 concerning Spatial Planning. This study also analyzes how spatial planning for the poor in Surabaya City is implemented. The research method used is normative juridical, with an analytical approach to documents and laws and regulations. The results indicate that Surabaya City's spatial planning policy plays a strategic role in supporting the realization of the PSN. However, its implementation remains problematic, such as a lack of spatial equity for the poor. The E-Rutilahu and Kampung Madani programs demonstrate more comprehensive sustainability in spatial planning. However, challenges and issues persist, ranging from limited budgets that hamper these programs, slow government bureaucracy in implementing regulations, and disruptions that occur in the field. This study recommends strengthening regulations, implementing social safeguards, and more meaningful public participation in spatial planning. In addition, this study also suggests replication and strengthening of the E-Rutilahu and Kampung Madani programs, as well as the use of spatial technology and big data in planning.